Gestión administrativa y su incidencia en el cumplimiento de las políticas institucionales de la cooperativa de ahorro y crédito Quevedo ltda. Del cantón Quevedo. Año 2015 - Álvarez García, Maria Fernanda (2016)
he development of cooperatives and businesses has been slower than other economic sectors. Now becomes important development of this sector. Management efficiency and effectiveness imparts to human efforts through timely achievement of goals, with the lowest possible costs and expenses. The administrative management is basic without it is not impossible to perform other complementary functions. institutional compliance officers within the credit union Ltda. Quevedo is analyzed in this research., to verify if the staff is knowledgeable about this issue in order to enable them to more effectively within the cooperative. The results show that the current system of administrative management of the credit union Quevedo Ltd., established that 57% of respondents you know about the system, 71% believe that this management could be improved, but by a change in model (71%), although 64% agree with the current management. When investigating policies administrative compliance that benefit the credit union Quevedo Ltda., It was found that 71% of respondents believe that compliance with policies optimize the management, most of them known institutional policies, 57% believe that there is compliance with those policies in the cooperative, although 57% believe that new policies benefit the institution. The functional processes of administrative management of the Cooperative are met by 57%, policy manuals and generate dynamism in the operation of the cooperative, although new processes for newly created new areas is required. This research evidence administrative management and compliance with institutional policies in the credit union Quevedo Ltda., And functions, and gives relevance to the administration as a conditioning factor performance of enterprises and cooperatives. Management is a necessary process to any collective effort whether public or private, civil or military, only varies the type of organization and management efforts adapts to each entity.